INVESTASI BERKELANJUTAN DAN KEUANGAN HIJAU DALAM EKONOMI SYARIAH - Rahmati, Arinal (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2025)
Sustainable investment and green finance have rapidly become prominent topics in the global financial landscape, with significant attention given to the environmental and social impacts of investment activities. In the context of Islamic economics, these concepts not only encompass economic benefits but also emphasize moral, ethical, and societal well-being. This article aims to explore the integration of sustainable investment, green finance, and Islamic economic principles, along with examples of countries that have successfully implemented these practices. The study also identifies existing challenges and opportunities, as well as their impact on sustainable development in Muslim-majority countries. Furthermore, this article highlights the role of Islamic financial institutions in supporting green investments and examines financial instruments that align with Shariah principles, such as green sukuk and productive waqf. By understanding the interaction between green finance and Islamic economics, it is expected that innovative strategies will emerge to enhance the financial sector's contribution to global sustainability